PERBANDINGAN FREE AIR ANOMALY AIRBORNE GRAVITY DENGAN EGM2008 PADA KETINGGIAN TERBANG (STUDI KASUS : PULAU KALIMANTAN) - Fathoni, Risman
In 2008-2011, the Geospatial Information Agency (BIG) in collaboration with DTU (Technical University of Denmark) measured gravity using Airborne Gravity technology to fill and complete the blanks of Indonesian gravity data. Apart from direct measurements, gravity information can be obtained practically through a global geopotential model. One of them, Earth Gravitational Model 2008 (EGM2008). The EGM2008 gravity information for the territory of Indonesia comes from the interpolation results of the SRTM (Forsberg and Kenyon) mission topography contained in the 5'x 5 'grid. From these two approaches (Airborne and EGM2008), we want to know the pattern of differences in the gravity information produced. This research is intended to visually compare the Airborne gravity with EGM2008 through a spatial approach. The comparison results show that EGM2008 has a gravity anomaly pattern similar to Airborne only in its longwave signal component, while in its short wave signal component, EGM2008 produces a gravity value that is almost close to zero / the signal is very weak. Meanwhile, on Airborne, the short wave signal is still strong and the appearance of the resulting pattern is still very fluctuating. This reinforces the reasons why, until now, Airborne gravity measurements are still needed.